2016
DOI: 10.1038/nbt.3554
|View full text |Cite
|
Sign up to set email alerts
|

A pigeonpea gene confers resistance to Asian soybean rust in soybean

Abstract: Asian soybean rust (ASR), caused by the fungus Phakopsora pachyrhizi, is one of the most economically important crop diseases, but is only treatable with fungicides, which are becoming less effective owing to the emergence of fungicide resistance. There are no commercial soybean cultivars with durable resistance to P. pachyrhizi, and although soybean resistance loci have been mapped, no resistance genes have been cloned. We report the cloning of a P. pachyrhizi resistance gene CcRpp1 (Cajanus cajan Resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 51 publications
1
65
0
2
Order By: Relevance
“…Since genetic resistance can provide effective and chemical-free disease control, many efforts are directed towards isolating rust-resistance genes in crop plants and understanding how to best deploy them for durable resistance [3]. In addition, related nonhost species are increasingly being utilised to identify new sources of resistance [4, 5]. Here, we summarise current knowledge of rust resistance, focussing on race-specific, non–race-specific, and nonhost resistance mechanisms.…”
mentioning
confidence: 99%
“…Since genetic resistance can provide effective and chemical-free disease control, many efforts are directed towards isolating rust-resistance genes in crop plants and understanding how to best deploy them for durable resistance [3]. In addition, related nonhost species are increasingly being utilised to identify new sources of resistance [4, 5]. Here, we summarise current knowledge of rust resistance, focussing on race-specific, non–race-specific, and nonhost resistance mechanisms.…”
mentioning
confidence: 99%
“…Kawashima et al reported that they cloned a Phakopsora pachyrhizi resistance gene, CcRpp1 , from pigeonpea ( Cajanus cajan ), and they showed that CcRpp1 conferred full resistance to P. pachyrhizi in soybean by applying map-based cloning approaches and transcriptome analysis [47]. …”
Section: Discussionmentioning
confidence: 99%
“…This R gene is expected to provide an alternative to the repeated use of foliar copper applications, benefiting both field workers and the environment [54]. Other examples of "mining" of R genes from related as well as unrelated plant species have been published for both monocots and dicots [47,55,56]. Recent research has also shown that it is possible to enhance disease resistance by modifying the target of a pathogen effector so that it recognizes other pathogen effectors [57].…”
Section: Mining R Genesmentioning
confidence: 99%